2012
DOI: 10.1161/strokeaha.111.642348
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the Magnetic Resonance Diffusion-Perfusion Mismatch Concept for Thrombolytic Patient Selection

Abstract: Background and Purpose-The DIAS-2 study was the only large, randomized, intravenous, thrombolytic trial that selected patients based on the presence of ischemic penumbra. However, DIAS-2 did not confirm the positive findings of the smaller DEDAS and DIAS trials, which also used penumbral selection. Therefore, a reevaluation of the penumbra selection strategy is warranted. Methods-In post hoc analyses we assessed the relationships of magnetic resonance imaging-measured lesion volumes with clinical measures in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 35 publications
(62 reference statements)
0
35
0
Order By: Relevance
“…[24][25][26] However, post hoc analyses suggested that a minimal mismatch volume of 60 mL would have led to a benefit in favor of desmoteplase. 27 Other intravenous thrombolytic phase 2 trials confirmed potential benefit in delayed treatment by using MR diffusion-perfusion imaging-based patient selection. 28,29 In the DEFUSE-2 trial, endovascular reperfusion was associated with a 5-fold increase in favorable clinical outcomes among patients with target mismatch (defined as ratio of Ͼ1.8), while no benefit was seen among patients without target mismatch.…”
Section: 13mentioning
confidence: 98%
“…[24][25][26] However, post hoc analyses suggested that a minimal mismatch volume of 60 mL would have led to a benefit in favor of desmoteplase. 27 Other intravenous thrombolytic phase 2 trials confirmed potential benefit in delayed treatment by using MR diffusion-perfusion imaging-based patient selection. 28,29 In the DEFUSE-2 trial, endovascular reperfusion was associated with a 5-fold increase in favorable clinical outcomes among patients with target mismatch (defined as ratio of Ͼ1.8), while no benefit was seen among patients without target mismatch.…”
Section: 13mentioning
confidence: 98%
“…Some prior data sets, including a post hoc analysis of the Desmoteplase in Acute Ischemic Stroke (DIAS) studies, demonstrated a treatment effect with an intravenous thrombolytic that was only present in patients with larger mismatch volumes. 19 Further studies of the benefit of endovascular therapy in patients with small mismatch volumes are warranted.The increased rate of PH in patients with the malignant profile confirms the findings of previous studies. 4,5 The trend toward fewer PH1 or PH2 hemorrhages in patients who did not have successful reperfusion is compatible with the established association between PH and large volume infarctions.…”
mentioning
confidence: 99%
“…However, the several multicentric studies which had been conceptualized around the mismatch hypothesis and its benefit for selecting patients for thrombolysis (DEFUSE, DIAS, DIAS II) also pointed to the many pitfalls of perfusion imaging, the first one being the very definition of mismatch. The initially popular idea that a sufficient mismatch was a difference of 20 % or more between PI and DWI soon proved too lenient [19] and likely played a pivotal role in ensuring the negative outcome of the DIAS II trial (published in 2009). Additionally, unlike DWI, perfusion imaging is not straightforward as the depiction (and subsequent potential volumetric assessment) of hypoperfusion is based on an array of different parameter maps and underlying calculation methods.…”
Section: Mismatch and Its Limitationsmentioning
confidence: 99%
“…However, the rather small number of patients with no target mismatches in their study greatly limited any ability to characterize the response to reperfusion in nonmismatch individuals. As a conclusion, the mismatch concept appears to function and provide useful information, but only under certain conditions, one of them being a large enough absolute mismatch volume, of somewhere between 15 and 60 ml, providing a sufficient amount of tissue to be saved in order for the results of successful reperfusion to be demonstrated [19]. Another would be a strict enough definition of hypoperfusion, serving to prevent areas of benign oligemia from being misinterpreted as tissue at risk of infarction [21,22].…”
Section: Mismatch and Its Limitationsmentioning
confidence: 99%